The Development of the Eco-Tense Game Book: A Non-Digital Game-Based Grammar Learning Media for Economics Students in South Papua - Pertiwi, Sri Ananda; Najdah T. (LETS: Journal of Linguistics and English Teaching Studies, 2026)
Mastery of English tense forms remains a persistent linguistic challenge for students in Papua, largely due to limited access to contextualized English learning resources, restricted digital connectivity, and unequal ownership of digital devices, particularly among indigenous Papuan students. To address these constraints, this study developed the Eco-Tense Game Book, a non-digital, game-based instructional medium designed for economics students. The development followed Plomp’s Research and Development (R&D) model, encompassing five stages: needs analysis, design, development, evaluation and revision, and implementation. Data were collected through semi-structured interviews and evaluation instruments administered to experts, practitioner, and students. The results showed that expert validation produced a high validity scoreof 91.5%, practitioner evaluation demonstrated good instructional feasibility with a score of 82.5%, and student evaluation revealed strong usability and learner acceptance, reflected in an overall score of 90.5%. The findings indicate that expert validation confirmed the academic appropriateness of the Eco-Tense Game Book, practitioner evaluation demonstrated its feasibility for classroom use, and student evaluation revealed that the media was easy for learners to use. The findings are based on validation and user perception data rather than experimental measurement of learning outcomes. A limitation of this study is the absence of a pre-test and post-test design to evaluate learning effectiveness. This study contributes to the development of non-digital game-based learning in English for Specific Purposes (ESP) by providing an alternative instructional resource for low-resource and low-connectivity educational settings.